Emotional Labor in ELT: A Systematic Review of Pre-Service Teachers’ Emotional Responses During Teaching Internships - Risty Dwi Paresi; Azwar Abbas (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
This study presents a systematic literature review analyzing the emotional experiences of pre-service teachers during their internship teaching practices in English Language Teaching (ELT). The concept of emotional labor is explored, focusing on how individuals manage their emotions to align with professional and societal expectations. The study identifies primary emotional responses, coping strategies, and their implications on teaching effectiveness, professional identity, and emotional well-being. A structured review protocol was followed, including specific inclusion and exclusion criteria, data extraction, and synthesis. The findings highlight the complex emotional dynamics pre-service teachers navigate, encompassing both positive and negative emotions influenced by various personal, organizational, and contextual factors. The review emphasizes the importance of supportive mentorship, constructive feedback, and a collaborative teaching environment in aiding pre-service teachers to manage emotional labor effectively.